Narratywizowanie przeszłości w cyfrowym ego-dokumencie na przykładzie gry autobiograficznej Cosmic Top Secret - Pigulak, Marcin (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The article addresses the problem of narrativizing the past in a digital ego-documentary using the example of the game Cosmic Top Secret (Klassefilm, 2018), directed by Trine Laier. The analysis combines a game studies perspective with the methodology of history, focusing on how an autobiographical game can serve as a vehicle for reflection on memory, identity, and historical experience. The central focus of the text is the game as a form of digital ego-document that emphasizes the subjective dimension of individual history (closely based on Laier’s personal experiences), situated within the broader context of the Cold War and historical culture (analysed in relation to Danish collective memory). The author analyses Laier’s design and narrative strategy, highlighting the use of historical sources, gameplay structures, and collage aesthetics. Cosmic Top Secret is presented as an example of a new form of autobiographical storytelling, in which interactivity fosters both personal engagement with the past and critical reflections on history.